2022
DOI: 10.21203/rs.3.rs-1891915/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of remifentanil and esketamine in combination with propofol for patient sedation during fiberoptic bronchoscopy: a randomized trial

Abstract: Background Ideal sedation and analgesia strategies for fiberoptic bronchoscopy have not been found. At present, propofol based sedation strategy still has some defects, such as respiratory depression and blood pressure drop, which is difficult to meet the requirements of safety and effectiveness at the same time. The aim of this study was to compare the clinical efficacy of propofol/remifentanil with propofol/esketamine for patient sedation during fiberoptic bronchoscopy. Method: Patients undergoing fiberopti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Esketamine, the newly marketed S-enantiomer of ketamine, has enhanced anesthetic effect [25] and reduced incidences of psychiatric side effects of ketamine [26]. The cardiovascular excitation effect of esketamine can provide stable mean arterial pressure and heart rate without signi cant uctuation [27][28][29]. Esketamine increases cardiac output in a dose-dependent manner and improves blood pressure stability and decrease the incidence of hypotension [30].As a result, esketamine provides better circulative stability and stable hemodynamics [31].…”
Section: Discussionmentioning
confidence: 99%
“…Esketamine, the newly marketed S-enantiomer of ketamine, has enhanced anesthetic effect [25] and reduced incidences of psychiatric side effects of ketamine [26]. The cardiovascular excitation effect of esketamine can provide stable mean arterial pressure and heart rate without signi cant uctuation [27][28][29]. Esketamine increases cardiac output in a dose-dependent manner and improves blood pressure stability and decrease the incidence of hypotension [30].As a result, esketamine provides better circulative stability and stable hemodynamics [31].…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have shown that propofol has emerged as a valuable agent for beroptic bronchoscopy due to its rapid induction of sedation or anesthesia, quick recovery, high clearance rate, and good tolerance [15,16]. Combining propofol with local anesthetics or opiates can further improve patient compliance by addressing coughing and a sense of asphyxiation are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have indicated that propofol has considered as a bene cial agent for FB due to its fast sedation or anesthesia onset, rapid recovery, high clearance rate, and high tolerance [15,16]. Combining propofol with local anesthetics or opiates can further improve patient compliance by alleviating coughing and reducing feelings of asphyxiation.…”
Section: Introductionmentioning
confidence: 99%